Training Needs of Clinical Psychologists in Screening and Follow-up Units for Health - Marouf, Zineb; Bordi, Malika Ben (Journal of Ecohumanism, 2025)
This research paper aims to highlight the training needs of clinical psychological specialists working in screening and follow-up units, considering these units as an embodiment of institutional policy within educational settings. The study employs a descriptive-analytical methodology, which goes beyond merely collecting information and describing the reality; it focuses on analyzing data and revealing the relationships between its dimensions to interpret them and reach conclusions that contribute to the development of the clinical psychological specialist’s work. Additionally, it seeks to provide support during clinical practice within the screening and follow-up units related to school health, particularly in working with individual or group student cases in the school environment. This is achieved by identifying the training needs necessary for effectively performing their duties within these units.